2008
DOI: 10.1007/s11103-008-9355-z
|View full text |Cite
|
Sign up to set email alerts
|

Lack of repeatable differential expression patterns between MON810 and comparable commercial varieties of maize

Abstract: The introduction of genetically modified organisms (GMO) in many countries follows strict regulations to assure that only products that have been safety tested in relation to human health and the environment are marketed. Thus, GMOs must be authorized before use. By complementing more targeted approaches, profiling methods can assess possible unintended effects of transformation. We used microarrays to compare the transcriptome profiles of widely commercialized maize MON810 varieties and their non-GM near-isog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
61
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(71 citation statements)
references
References 41 publications
9
61
0
1
Order By: Relevance
“…Metabolome analysis of Bt-maize by NMR also revealed significant differences in free amino acid contents of the parental line; however, other likely-influential factors were not assessed in this study (9). Comparative transcript profiling of different maize cultivars harboring an identical Bt transgene insertion event revealed that the variability between cultivars was much greater than the influence of the transgene (10,11). Independently, comparison of the potato tuber proteome of 21…”
mentioning
confidence: 66%
“…Metabolome analysis of Bt-maize by NMR also revealed significant differences in free amino acid contents of the parental line; however, other likely-influential factors were not assessed in this study (9). Comparative transcript profiling of different maize cultivars harboring an identical Bt transgene insertion event revealed that the variability between cultivars was much greater than the influence of the transgene (10,11). Independently, comparison of the potato tuber proteome of 21…”
mentioning
confidence: 66%
“…When performing transcriptomic studies using in vitro-or field-grown maize (Zea mays) plants, Coll et al (2008Coll et al ( , 2009 found differential expression for a minority of transcripts between in vitro-grown MON810 (insectresistant of Bt type) and control lines, and most of these differences were not observed in the field. In real agricultural conditions, under two farming practices (conventional and low-nitrogen fertilization), Coll et al (2010a) found differential expression for only 0.14% of the analyzed sequences (approximately one-third of the maize genome).…”
Section: Maizementioning
confidence: 99%
“…An alternative with much greater power is to adjust P-values to control the probability that each declared difference is significant (CurranEverett, 2000). This can be accomplished using a False Discovery Rate (FDR) control procedure (Benjamini and Hochberg, 1995), which is a commonly used approach in studies examining transgenic crops (Herman et al, 2007;Coll et al, 2008;Huls et al, 2008;Jacobs Dow AgroSciences LLC et al, 2008;Stein et al, 2009;Herman et al, 2010). Therefore, the P-values from the contrasts were each adjusted using the FDR method to improve discrimination of true differences among treatments from random effects (false positives).…”
Section: Data Collection and Statistical Analysismentioning
confidence: 99%